(untitled) (Research, Society and Development, 2022)
Objective: To identify what the literature reveals about sociability as a motivation for the elderly to practice physical activity. Method: The present study was carried out through a bibliographical research, bringing a survey of scientific articles in the Google Scholar database, locating 33,800 studies. After using the filters, the numbers were reduced to 38 studies. A search selection by title and abstract was performed, totaling 18 articles. After a thorough check, only seven studies were selected for the search. Results: The results showed that sociability was present as an important motivational factor in all selected studies, showing the importance of physical activity in contributing to social interaction and building bonds for the elderly. Conclusion: It was concluded that sociability was one of the main motivational determinants that most led elderly individuals to practice physical activity.